Pengaruh Kesadaran Pajak, Sanksi Pajak, dan Sistem Perpajakan terhadap Persepsi Penggelapan Pajak - Hakki, Tandry Whittleliang; Simanungkalit, Jobrinson; Surjadi, Merna; Loanza, Marshia (Dinasti Research, 2025)
The Ministry of Tourism and Creative Economy has targeted to mentor 100 startups through the IndoBisa 2024 program. Young entrepreneurs in the early stages of their businesses need tax education to become compliant taxpayers and avoid tax evasion. This study aims to analyze the influence of Tax Awareness, Tax Sanctions, and the Taxation System on young entrepreneurs’ intention to commit tax evasion. A quantitative approach was employed using primary data collected from HIPMI members in Jakarta and East Java. The sampling technique used was purposive sampling. Hypotheses were tested using multiple linear regression analysis with SPSS. The results show that: (1) Tax Awareness has a negative and significant effect on tax evasion intention; (2) Tax Sanctions have a positive and significant effect on tax evasion intention; and (3) the Taxation System also has a positive and significant effect on tax evasion intention.